(untitled) (Orfeu, 2019)
Based on references to the study of the song in the History and the History of the Present Time, the article discusses the song Camila Cabello’s Havana (ft. Young Thug), released in 2017. Through the articulation between song and music video, to discuss approaching music as a fluid and relational process in certain contexts (GONZALEZ, 2016), as well as articulating representations around the Latin issue in the United States, based on relationships with temporalities. As a theoretical-methodological assumption, we start from the perspective of narrative analysis to understand the processes of story making, intrigue and representation through symbolic constructions and the ordering of temporalities in the song and its clip. The study made it possible to understand some characteristics that involve phenomena of the history of pop music contributing to the discussion about the song in the contemporary cultural industry.